PERAN GAMBUT TERHADAP NITROGEN TOTAL TANAH DI LAHAN RAWA - Arifin Fahmi; Bostang Radjagukguk (BERITA BIOLOGI, 2013)
Peatland has important role in wetland ecosystem stability. Depletion and disappearance of peat layer lead to loss of potential source of nutrient and disruption of wetland ecosystem stability. The research aimed to study the influence of peat thickness and land hydrological condition on the total nitrogen (N) content in soil, the influence of rapidly or naturally the depletion and disappear of peat layer on total N content in soil, and the influence of hydrological condition on total N content in soil. Total N was observed in June of 2009 and 2010 (transition from wet to dry season), September of 2009 and 2010 (peak of dry season), and January of 2010 and 2011 (peak of wet season). The research was carried out on potential acid sulphate soil (A), peaty acid sulphate soil (B),shallow peat which all of peat layers wereremoved (C), shallow peat which peat layer was partially removed (D), shallow peat (E), moderate peat (F) and deep peat (G). The results showed that total N content increased with increasing of peat thickness, the depletion and disappearance of peat layer reduced total N content in soil, and declining in the groundwater level increased total N content in soil.